2021
DOI: 10.1101/2021.08.05.455317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peptidergic modulation of fear responses by the Edinger-Westphal nucleus

Abstract: Many neuronal populations that release fast-acting excitatory and inhibitory neurotransmitters in the brain also contain slower acting neuropeptides. These facultative peptidergic cell types are common, but it remains uncertain whether obligate peptidergic neurons exist. Our fluorescence in situ hybridization, genetically-targeted electron microscopy, and electrophysiological characterization data strongly suggest that neurons of the non-cholinergic, centrally-projecting Edinger-Westphal nucleus in mice are fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 119 publications
2
18
0
Order By: Relevance
“…Injection of tracers showed that these midline neurons project to many different brain regions, both rostrally and caudally, and constitute what is known as the “centrally projecting EW” (EWcp), distinct from the cholinergic peripherally projecting neurons ( Dos Santos Júnior et al., 2015 ; Kozicz et al., 2011 ). Recently, behavioral studies have shown that the activity of murine EWcp neurons increases arousal during tasks involving conditioning ( Lovett-Barron et al., 2017 ), memorization ( Li et al., 2018 ), or fear modulation ( Priest et al., 2021 ). Moreover, neurons of this region control the transitions between sleep phases ( Zhang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Injection of tracers showed that these midline neurons project to many different brain regions, both rostrally and caudally, and constitute what is known as the “centrally projecting EW” (EWcp), distinct from the cholinergic peripherally projecting neurons ( Dos Santos Júnior et al., 2015 ; Kozicz et al., 2011 ). Recently, behavioral studies have shown that the activity of murine EWcp neurons increases arousal during tasks involving conditioning ( Lovett-Barron et al., 2017 ), memorization ( Li et al., 2018 ), or fear modulation ( Priest et al., 2021 ). Moreover, neurons of this region control the transitions between sleep phases ( Zhang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The identity of this second target population is presently unknown. Neurons that use peptidergic neurotransmission and do not co-release glutamate or GABA have recently been described in the Edinger-Westphal nucleus medial and ventral to the PAG 58 whose CART + neurons were shown to modulate fear responses in rodents 58 . Neurons releasing peptidergic neuromodulators have been described in dPAG 59 , including a population that releases enkephalins 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurons that use peptidergic neurotransmission and do not co-release glutamate or GABA have recently been described in the Edinger-Westphal nucleus medial and ventral to the PAG 39 whose CART+ neurons were shown to modulate fear responses in rodents 39 . Neurons releasing peptidergic neuromodulators have been described in dPAG 40 , including a population that releases enkephalins 41 .…”
Section: Discussionmentioning
confidence: 99%